Determinants of Poverty in Indonesia: A Recursive Equation Approach - Lifriyadi Lifriyadi; Restiatun Restiatun; Yarlina Yacoub (Universitas Gadjah Mada, 2026)
Despite continuous improvements in the Human Development Index (HDI), Indonesia’s poverty rate remained relatively high at 8.57 percent in 2024, indicating persistent structural challenges. This indicates a critical gap in variables determining poverty in Indonesia. This study aims to analyse the determinants of poverty across Indonesian provinces by examining both indirect and direct transmission mechanisms. The study employs a quantitative explanatory design using a two stage recursive panel data model that integrates regional financial effectiveness, regional financial efficiency, provincial minimum wages, HDI, and domestic investment. Secondary data are obtained from the Directorate General of Fiscal Balance (DJPK), Ministry of Finance of the Republic of Indonesia, and Statistics Indonesia (BPS), covering 34 provinces over the 2018 to 2024 period with 238 observations. A balanced panel dataset is estimated using panel data techniques, and the Fixed Effects model is selected based on the Hausman test. The results show that regional financial effectiveness and provincial minimum wages positively affect HDI, while fiscal inefficiency reduces human development. HDI significantly reduces poverty, confirming its mediating role, whereas domestic investment has a direct negative effect on poverty. These findings highlight the importance of coordinated fiscal and investment policies to accelerate poverty reduction